The quest for indicators of paroxysmal atrial fibrillation in sinus rhythm – the DETECT AF trial. Issue 4 (4th July 2019) - Brasier, N.; Engelter, S.; Kolbitsch, T.; Tabord, A.; Knobeloch, J.; Kühne, M.; Conen, D.; Traenka, C.; Kreutzberger, T.; Völlmin, G.; Eckstein, J.
Abstract: Background: Atrial fibrillation (AF) is related to an increased stroke risk. At present, differentiation between patients with paroxysmal AF (pAF) and without is only possible during AF episodes and not during sinus rhythm. If AF could be diagnosed more quickly and reliably, anticoagulation therapy may be administered and prevent from cardioembolic strokes. The DETECT AF trial evaluated the hypothesis that propagation of electric activities in patients with pAF differs from propagation in healthy atria and that this can be detected with a three-dimensional electrocardiogram in patients during sinus rhythm. Methods: We conducted a case-control study including patients with a history of pAF and a control group with no history of AF. Vectorcardiographic beat-to-beat variability of atrial activation in sinus rhythm was tested and compared between the two groups. Results: One hundred and eight patients with a history of pAF in sinus rhythm and 121 controls in sinus rhythm were included. With a combination of specific vectorcardiographic beat-to-beat variability parameters discrimination between the two groups was possible with a specificity of 82% and a sensitivity of 71% ( p ≤.01). Using heart rate independent parameters, both specificity and sensitivity were reduced to 70%. Conclusions: Analysis of atrial vectorcardiographic beat-to-beat variability indicates that atrial conduction variability in patients with pAF differs from patients without AF and may be used as an indicator to estimate the risk for pAF in patients during sinus rhythm. Further studies to investigate the potential of this parameter are needed. Trial registration: ClinicalTrials.gov identifier: NCT02270112.